Enemy combatants, terrorism, and armed conflict law a guide to the issues (Praeger Security International, 2008)
With a renewed emphasis on national and homeland security, the United States is once again seeking to balance the needs of the state with the rights of its citizens as well as those of other nations. This set represents an approach to the legal dilemmas borne out by the war on terror.